CIA's analysis of the Soviet Union, 1947-1991 : a documentary collection - Editors: Gerald K. Haines, Robert E. Leggett. (Center for the Study of Intelligence, Central Intelligence Agency, 2001)
Includes bibliographical references. Also available via the Internet: http://www.cia.gov/csi/books/princeton/